Association between sleep during pregnancy and birth outcomes: a prospective cohort study - Libing Huang; Huanjun Chen; Fuhui Yao; Zhonghan Sun; Shijiao Yan; Yuwei Lai; Chuanzhu Lv; Xiong-Fei Pan; Rixing Wang; Xingyue Song (Reproductive Biology and Endocrinology)
Abstract Objective A prospective cohort study was conducted to investigate sleep status during the early and second trimester of pregnancy in pregnant women on adverse birth outcome, such as preterm birth, low birth weight and small for gestational age. Methods Multivariable logistic regression models were used to analyze the association of sleep status during the early and second trimester of pregnancy with adverse birth outcomes and generated the odds ratio and 95% confidence interval. Results 5,418 pregnant women were included in the analysis. In the multivariable model, compared with 7.1–8 h/night, sleep ≤ 7 h/night during second trimester increases the risk of preterm birth (OR: 1.43, 95% CI: 1.12,1.85), and the risk of preterm birth was decreased in pregnant women who slept > 9 h/night (OR: 0.79, 95% CI: 0.53,0.93). Sleep quality, and sleep changes in the early and second trimesters, and sleep duration in the early pregnancy were not statistically associated with preterm birth, low birth weight and small for gestational age. Conclusions Short sleep duration during pregnancy is associated with a higher risk of preterm birth and longer sleep duration at night is associated with a lower risk of preterm birth, but the latter needs further verification. Sleep status during pregnancy was not associated with low birth weight and small for gestational age. In order to reduce risk of adverse birth outcomes, sleep problems in pregnant women should be strengthened during pregnancy care. Clinical trial number Not applicable.